A reflection of the lower rate of infectivity among comorbid conditions in multidrug-resistant tuberculosis - Smitha Thungathurthi, Prabhakar Orsu (Journal of Applied Pharmaceutical Science, 2022)
Tuberculosis (TB) is one of the main causes for death among people worldwide. There has been an increase in the incidence of drug-resistant TB. The effect of TB on various diseases has an impact on hematological parameters and it is an emerging problem in India. The impact of the medical condition on diabetes, hypothyroid, and retroviral disease (RVD) in multidrug resistance TB is investigated. The study highlights changes in hematological parameters in both genders. The study enrolled (N = 271) patients with drug resistance attending the district government hospital. The study observed normocytic normochromic anemia (n = 244) in most patients. Anemia was prevalent in female (n = 68) patients. A statistical significance was observed in hemoglobin (p < 0.0001***), hematocrit (p < 0.0001***), red cell indices between male and female patients. The study reported the drug-resistant TB more in diabetes than in hypothyroid and RVD patients. The clinical conditions such as diabetes, hypothyroid, RVD in multidrug resistance TB established significant changes in cell counts of white cells (p = 0.03* ), monocytes (p < 0.0002***), and immature granulocytes (p < 0.009**). Monitoring anemia in TB is essential, and it is pertinent to monitor anemia in female patients as a prerequisite. The drug resistance TB worsened the hematological parameters compared to the comorbid conditions with drug resistance TB.
Keywords: Drug-resistant tuberculosis, hematological parameters, gender, medical conditions, differences